INVASIVE ASPERGILLOSIS IN CHILDREN: UPDATE ON CURRENT GUIDELINES - Athanasia Apsemidou; Nikolaos Petridis; Timoleon-Achilleas Vyzantiadis; Athanasios Tragiannidis (Mediterranean Journal of Hematology and Infectious Diseases)
Invasive aspergillosis (IA) is an important cause of infectious morbidity and mortality in immunocompromised paediatric patients. Despite improvements in diagnosis, prevention and treatment, IA is still associated with high mortality rates. To address this issue, several international societies and organisations have proposed guidelines for the management of IA in the paediatric population. In this article, we review current recommendations of the Infectious Diseases Society of America, the European Conference on Infection in Leukaemia and the European Society of Clinical Microbiology and Infectious Diseases for the management and prevention of IA in children.